Diseño de modelo en gestionamiento del conocimiento empresarial para garantizar transparencia asertiva en el conocimiento de una compañía (2021)
To manage business knowledge, different techniques can be used, in the first instance it must be determined which skills are essential for the company. These depend on the nature of their activity, in addition to the environment in which they operate. Some procedures to manage knowledge we can mention the following: First we can say, the internal study lies in offering courses and training to its employees, expanding the intellects about defined activities, the optimal, objective and useful information for the company. A second will be teamwork. There are certain events that depend on the experience of the employees themselves; they are those subjective points of view that are in the person's own knowledge. The best way to achieve this objective is to promote teamwork, in this way the staff will be able to transmit their knowledge to their colleagues, thus creating a collective knowledge.